Paracostal Eventration of a Pregnant Uterus in a Bitch - Rocha, Nadyne Lorrayne Farias Cardoso; Bahr Arias, Mônica Vicky (Acta Scientiae Veterinariae, 2020)
Background: Traumatic abdominal hernias result from trauma which causes muscular and fascia rupture, with dislocation of viscera into the subcutaneous space without perforation of the skin. Paracostal eventration, occurs due to avulsion of the abdominal external oblique and abdominal transverse muscles from their insertion point at the ribs, resulting in dislocation of the abdominal viscera into the subcutaneous region, lateral to the abdominal wall; however, there are few reports in the literature describing this type of lesion in dogs, especially when the herniated content is a gravid uterus. The purpose of this paper is to report a case of traumatic paracostal hernia of a pregnant uterus in a dog. Case: A 2-year-old pregnant bitch weighing 8.9 kg was presented with a sudden increase in abdominal volume lateral to the left thoracic wall which, according to the owner, started after the dog was hit by a car. On physical examination, the dog had a greenish vaginal secretion and the increased volume on the left paracostal region mentioned above. Laboratory exams showed normocytic normochromic anemia, slight leukocytosis without a shift, and a discreet increase in creatinine, urea, and alanine aminotransferase. Abdominal radiographs showed a lack of continuity of the left abdominal muscle wall, with passage of the uterine horn into the subcutaneous space lateral to the rib cage. After stabilization of the patient with fluid therapy and analgesia, the bitch was anesthetized with propofol intravenously, and maintained with isoflurane diluted in oxygen. Cephazolin was administered intravenously 30 min prior to the surgery as prophylactic antibiotic therapy. An exploratory celiotomy was then performed, where a defect in the internal and external oblique abdominal muscles and transverse abdominal muscle was observed at their point of origin and insertion at the thirteenth rib. The left uterine artery and vein were also observed to be compromised, with several areas of hemorrhage noted on the left uterine horn. Surgical repair of the muscle defect was performed, anchoring the affected muscles to the rib. Ovariohysterectomy was performed after fetal death was confirmed. Patient recovery was uneventful after the procedure. Discussion: Paracostal eventration is the rarest type of herniation in small animals, and the fact that the uterus was dislocated in this case makes it even more atypical. A complete physical examination with special attention to the abdominal contour is extremely important in patients that have suffered trauma. The most characteristic sign of paracostal eventration is the change in abdominal and thoracic wall contours, as observed in the present report. Exploratory surgery is recommended as quickly as possible and as soon as the patient is stable enough to be anesthetized since this is an acute eventration with a risk of incarceration of the affected organs. In the present case, because it was a pregnant uterus, there was the risk of organ rupture or toxemia due to fetal death, which could bring more complications to the patient; these risks justify a ovariohysterectomy. The transverse abdominal and external and internal oblique abdominal muscles were anchored onto the last rib, as described in the literature. In conclusion, diagnosis of a paracostal eventration was possible from the medical history, physical exam, imaging studies, as well as exploratory celiotomy to evaluate the extent of the muscular defect and visceral damage and also to allow surgical correction. Suture of the abdominal musculature with anchorage to the thirteenth rib was an effective treatment.